Immunological Changes in Peripheral Blood of Ankylosing Spondylitis Patients during Anti-TNF-α Therapy and Their Correlations with Treatment Outcomes - Rongjuan Chen; Hongyan Qian; Xiaoqing Yuan; Shiju Chen; Yuan Liu; Bin Wang; Guixiu Shi (Journal of Immunology Research)
Tumor necrosis factor-α (TNF-α) inhibitors are the main types of biological conventional synthetic disease-modifying antirheumatic drugs and have efficacy in treating ankylosing spondylitis (AS) which is not sensitive for nonsteroidal anti-inflammatory drug. However, the impact of TNF-α inhibitors on immune cells in patients with AS is still clearly undefined, and the impact of immune cells on treatment response is also largely elusive. This study is aimed at evaluating the longitudinal changes of circulating immune cells after anti-TNF-α therapy and their associations with treatment response in AS patients. Thirty-five AS patients receiving the treatment of anti-TNF-α therapy were included into this prospective observational study. The frequencies of immune cells including Th1, Th2, Th17, regulatory T cell (Treg), T follicular helper cell (Tfh), and regulatory B cell (Breg) in the peripheral blood were measured by flow cytometry at baseline and 4 time points after therapy. The difference in the circulating immune cells between responders and nonresponders was compared. This study suggested that anti-TNF-α therapy could significantly reduce circulating proinflammatory immune cells such as Th17 and Tfh, but significantly increased the percentages of circulating Treg and Breg. Moreover, circulating Breg may be a promising predictor of response to anti-TNF-α therapy in AS patients.